2001
DOI: 10.1007/s003840100298
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-depletion of blood components does not significantly reduce the risk of infectious complications

Abstract: Allogeneic blood transfusions are claimed to be an independent risk factor for postoperative infections in open colorectal surgery due to immunomodulation. Leukocyte-depletion of erythrocyte suspensions has been shown in some open randomized studies to reduce the rate of postoperative infection to levels observed in nontransfused patients. Using a double-blinded, randomized design, we studied the postoperative infection rate in patients undergoing open colorectal surgery transfused with either leukocyte-deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
114
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(116 citation statements)
references
References 15 publications
2
114
0
Order By: Relevance
“…3 However, it has been noted that a leukodepleted RBC unit can contain up to one million donor leukocytes and still be within specification under the Council of Europe guidelines and clinical studies suggest that RBC transfusion is still associated with undesirable transfusion outcomes. 4,5 One such undesirable outcome is termed microchimerism, which is the co-existence of small numbers of genetically disparate cell populations within a single host. 6 Usually transfused donor cells are recognized by the recipient immune system and are removed within a few days of transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, it has been noted that a leukodepleted RBC unit can contain up to one million donor leukocytes and still be within specification under the Council of Europe guidelines and clinical studies suggest that RBC transfusion is still associated with undesirable transfusion outcomes. 4,5 One such undesirable outcome is termed microchimerism, which is the co-existence of small numbers of genetically disparate cell populations within a single host. 6 Usually transfused donor cells are recognized by the recipient immune system and are removed within a few days of transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 13 RCTs on leukodepleted blood transfusions in different clinical settings evaluated postoperative infections as a primary or secondary endpoint [31][32][33][34][35][36][40][41][42][43][44][45][46]. These studies included singleand multicenter designs, clinical diagnosis, methods for documenting and reporting infections, and the proportion of transfused patients (range: 14%-95%).…”
Section: The Clinical Effects Of Allogeneic Leukocytes In Cardiac Surmentioning
confidence: 99%
“…These studies included singleand multicenter designs, clinical diagnosis, methods for documenting and reporting infections, and the proportion of transfused patients (range: 14%-95%). Among them, 5 included patients undergoing colorectal or gastrointestinal surgery [40][41][42][43][44], 1 was performed with patients undergoing aortic aneurysm repair or resection of gastrointestinal malignancy [45], and 1 included trauma patients [46]. The postoperative infection results in these RCTs, which were conducted with different patient populations using different study designs, are inconsistent.…”
Section: The Clinical Effects Of Allogeneic Leukocytes In Cardiac Surmentioning
confidence: 99%
“…The recurrence of cancer was explored in only one study in patients with colorectal cancer, in which there was no advantage of removing leucocytes from transfusions. 11 Five prospective randomised studies investigated the incidence of postoperative infections after abdominal surgery by [11][12][13][14][15] comparing outcome after transfusions of non-filtered red blood cells or red blood cells with leucocytes filtered out. Three of these trials [13][14][15] observed a reduction and two 11 12 found a similar incidence of postoperative infections after filtered transfusions.…”
Section: Introductionmentioning
confidence: 99%